Import Replacement - As an Assistant Mechanism for Diversification of Production and Approval of Foreign Trade - Solijonovna, Sobitova Rano (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the essence of import substitution, its purpose, its importance in the economic development of the country.